Crustal deformation on the Chinese mainland during 1998–2014 based on GPS data - Bin Zhao; Yong Huang; Caihong Zhang; Wei Wang; Kai Tan; Rinlin Du (Geodesy and Geodynamics, 2015)
This study focuses on resolving moderate amounts of crustal motion at the continental scale based on a large volume of global positioning system (GPS) data during 1998–2014. A state-of-the-art GPS processing strategy was used to resolve position time series and velocities from carrier beat phases for all available data. Position time series were closely analyzed to estimate linear constant, coseismic displacements, postseismic motions, and other parameters. We present coseismic offsets inferred from the GPS data for the 2010 Yushu and 2014 Yutian earthquakes, and also illustrate transient postseismic motions following the 2001 Kokoxili, 2008 Wenchuan, and 2011 Tohoku-Oki earthquakes. Since not all GPS position time series dominated by postseismic motions can be modeled and corrected reasonably, we present contemporary horizontal velocities from 2009 to 2014 for campaign stations and from 1998 to 2014 for continuous stations, irrespective of postseismic deformations. Our study concludes that we need to accumulate observations over a greater duration and apply accurate postseismic modeling to correct for transient displacement in order to resolve reasonable interseismic velocity.